Pengaruh Literasi Keuangan Penggunaan Informasi Akuntansi dan Modal Usaha Terhadap Keberlanjutan UMKM di Kecamatan Buleleng - Gst. Ayu Ketut Rencana Sari Dewi; Ayu, Ni Cening Putri Eka (Vokasi : Jurnal Riset Akuntansi, 2021)
This quantitative approach research aims to determine the influence of financial literacy, the use of accounting information, and business capital on the sustainability of micro, small and medium businesses in buleleng district. Sample size is determined through Isaac Michael formula, so that 68 MSMEs are obtained by selecting respondents using probability sampling The data sources in this study are primary and secondary data. The method of data collection is carried out by the dissemination of questionnaires. The data analysis method used is multiple linear regression tests. The data was analyzed using SPSS version 26.0 for windows. The results of this study show that: (1) financial literacy has a positive and significant effect on the sustainability of MSMEs in Buleleng Sub-district; (2) the use of accounting information has a positive and significant effect on the sustainability of MSMEs in Buleleng Sub-district; and business capital have a positive and significant effect on the success of MSMEs in Buleleng sub-district